2020
DOI: 10.1080/23322039.2020.1719574
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive market hypothesis: An empirical analysis of time –varying market efficiency of cryptocurrencies

Abstract: This study examines the adaptive market hypothesis (AMH) in relation to time-varying market efficiency by using three tests, namely Generalized Spectral (GS), Dominguez-Lobato (DL) and the automatic portmanteau test (AP) test on fourdigital currencies; Bitcoin, Monaro, Litecoin, and Steller over the sample period of 2014-2018. The study applies Jarque-Bera test, ADF test, Ljung-Box statistics and ARCH-LM test for testing normality of returns, stationarity of series, serial correlation and volatility clustering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Further, we want to test a complex relationship in this study, and GAM is one of the most suitable methods to test highly complex nonlinear relationships along with a huge number of complex potential predictors. Past studies highlighted the significance of using robust statistical methods in empirical studies (Mustafa et al 2018;Nasir et al 2020;Khursheed et al 2020aKhursheed et al , 2020b. Therefore, we applied GAM with a quasi-Poisson link function based on its significance in testing highly complicated relationships (Chen et al 2017a(Chen et al , 2017bRavindra et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Further, we want to test a complex relationship in this study, and GAM is one of the most suitable methods to test highly complex nonlinear relationships along with a huge number of complex potential predictors. Past studies highlighted the significance of using robust statistical methods in empirical studies (Mustafa et al 2018;Nasir et al 2020;Khursheed et al 2020aKhursheed et al , 2020b. Therefore, we applied GAM with a quasi-Poisson link function based on its significance in testing highly complicated relationships (Chen et al 2017a(Chen et al , 2017bRavindra et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous previous studies have focused on market efficiency testing several versions of the EMH. Some focus on market efficiency in the energy markets (Khediri & Charfeddine, 2015;Ghazani & Ebrahimi, 2019), bond markets (Charfeddine et al, 2018), stock markets (Alvarez-Ramirez et al, 2012;Urquhart & Hudson, 2013;Hiremath & Kumari, 2014;Rodriguez et al, 2014;Xiong et al, 2019), commodities markets (Shahid et al, 2019a), cryptocurrencies (Khursheed et al, 2020) and foreign exchange markets (Charles et al, 2012) within the framework of AMH.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Their findings suggest that the return predictability of foreign exchange rates varies over time depending on market conditions. Khursheed et al (2020) examined the AMH in cryptocurrency markets (such as bitcoin, Monaro, litecoin, and steller) using generalized spectral, Dominguez-Lobato, and the automatic portmanteau test for the period of 2014-2018 and concluded that the predictability varies over time.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…This also supports the EMH and also encourages researchers to study the same effect on other CCYs. Khursheed, Naeem, Ahmed, and Mustafa (2020) studied the time varying market efficiency with relation to AMH. The paper uses three different methods including generalized spectral, automatic portmanteau and Dominguez-Lobato tests.…”
Section: Adaptive Market Hypothesesmentioning
confidence: 99%